The Cholinergic Amelioration of Sepsis-Induced Baroreflex Dysfunction and Brainstem Inflammation Is Negated by Central Adenosine A3 Receptors - Amany E. El-Naggar; Mai M. Helmy; Sahar M. El-Gowilly; Mahmoud M. El-Mas (Pharmaceuticals)
Background/Objectives: Sepsis has been shown to depress arterial baroreceptor function, and this effect is counterbalanced by the cholinergic anti-inflammatory pathway. Considering the importance of central adenosine receptors in baroreceptor function, this study tested whether central adenosine A3 receptors (A3ARs) modulate the cholinergic-baroreflex interaction in sepsis and whether this interaction is modulated by mitogen-activated protein kinases (MAPKs) and related proinflammatory cytokines. Methods: Sepsis was induced by cecal ligation and puncture (CLP) and rats were instrumented with femoral and intracisternal (i.c.) catheters. Baroreflex sensitivity (BRS) was measured 24 h later in conscious animals using the vasoactive method, which correlates changes in blood pressure caused by i.v. phenylephrine (PE) and sodium nitroprusside (SNP) to concomitant reciprocal changes in heart rate. Results: The reduction in reflex bradycardic (BRS-PE), but not tachycardic (BRS-SNP), responses elicited by CLP was reversed by i.v. nicotine in a dose-related manner. The BRS-PE effect of nicotine was blunted following intracisternal administration of IB-MECA (A3AR agonist, 4 µg/rat). The depressant action of IB-MECA on the BRS facilitatory action of nicotine was abrogated following central inhibition of MAPK-JNK (SP 600125), PI3K (wortmannin), and TNFα (infliximab), but not MAPK-ERK (PD 98059). Additionally, the nicotine suppression of sepsis-induced upregulation of NFκB and NOX2 expression in the nucleus tractus solitarius (NTS) was negated by A3AR activation. The molecular effect of IB-MECA on NFκB expression disappeared in the presence of SP 600125, wortmannin, or infliximab. Conclusions: The central PI3K/MAPK-JNK/TNFα pathway contributes to the restraining action of A3ARs on cholinergic amelioration of sepsis-induced central neuroinflammatory responses and impairment of the baroreceptor-mediated negative chronotropism.